Legal Protection for Witnesses and Victims of Crimes of Terrorism - Umam, Muhammad Miftahul; Arifin, Ridwan (Faculty of Law Universitas Negeri Semarang, 2022)
Terrorism is a form of extraordinary crime that is an enemy to mankind. Terrorism throughout history has been a very frightening specter. This is inseparable from the impact it causes, the loss is not only property, life, physical, psychological, but also creates an atmosphere of terror that grips all levels of society. Therefore, victims and witnesses of acts of terrorism must receive protection in view of these various things. As a state of law, Indonesia has established several laws and regulations governing the protection of victims of terrorism, including Law no. 15 of 2003, as amended by Law no. 5 of 2018 concerning Amendments to Law Number 15 of 2003 concerning Stipulation of Government Regulations in Lieu of Law Number 1 of 2002 concerning Eradication of Criminal Acts of Terrorism into Law, Law no. 13 of 2006, as amended by Law no. 31 of 2014 concerning Amendments to Law Number 13 of 2006 concerning the Protection of Witnesses and Victims and other regulations. With the existence of a legal footing that regulates, it is hoped that it can provide protection for witnesses and victims of acts of terrorism. In addition, various parties also play a role in the recovery of victims from acts of terrorism, including; police institutions, social services, hospitals, Kesbangpol, PMI, NGOs, LPSK, and so on. However, witnesses and victims of criminal acts of terrorism in obtaining legal protection through the above regulations are not always in line with the existing reality. This is inseparable from the existence of inhibiting factors, both in the aspect of legal substance, legal structure, and legal culture components.